Port Authority of Trinidad and Tobago Port of Spain: Plan 2000 - A technical and economic analysis of future development opportunities. Volume II, Land use plan draft final report. - Novaport. (Novaport., 2011)
Presents information on the future of the port, an economic analysis, facilities for traditional port facilities and land use in the Central Business District of Port of Spain.
Keywords: Port Authority of Trinidad and Tobago (PATT), Industrial development - Trinidad and Tobago, Physical planning – Ports, Development planning - Central business districts, Ports - Economic aspects, Sea Lots, Port-of-Spain Waterfront, Cruise Ship Complex.